2021
DOI: 10.1111/myc.13402
|View full text |Cite
|
Sign up to set email alerts
|

Dysbiosis of skin mycobiome in atopic dermatitis

Abstract: Atopic dermatitis (AD) is a chronic and relapsing inflammatory skin disease with an increasing prevalence worldwide. The aetiology and pathogenesis of AD have not been fully elucidated. Previous studies have suggested the role of fungi as a triggering factor in the development AD. Here we conducted a systematic review to investigate the skin mycobiome profiles in AD and to address whether there is an association between fungal dysbiosis and AD. We searched Medline/PubMed, Embase and Web of Science for research… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 22 publications
(14 citation statements)
references
References 57 publications
0
12
0
2
Order By: Relevance
“…These include the fungal family Malassezia spp. [8,9]. These lipophilic fungi require an alkaline pH for growth.…”
Section: Discussionmentioning
confidence: 99%
“…These include the fungal family Malassezia spp. [8,9]. These lipophilic fungi require an alkaline pH for growth.…”
Section: Discussionmentioning
confidence: 99%
“…Antifungal immune system responses include C-type lectin receptors, IL-1β, and inflammasomes [ 59 ]. In atopic dermatitis skin lesions, it has been found that Malassezia levels are decreased, and filamentous fungi are increased, along with a positive correlation between Candida and Staphylococcus [ 60 ]. Understanding and elucidating mycobiome implications of this nature could help in the development of more effective treatments for the ailments [ 58 ].…”
Section: Mycobiome Dysbiosismentioning
confidence: 99%
“…25,102 Dysbiosis of the skin microbiota is associated with skin disorders such as AD. Lesional skin of AD patients features increased diversity in the mycobiome with a concomitant decrease in the abundance of Malassezia spp., 31,103 as well as a dominance of Staphylococcus aureus 104,105 in the bacterial compartment. S. aureus is widely accepted as a driver of disease pathogenesis in AD.…”
Section: Microbial Interactions In the Skin Shaping Cutaneous Patholo...mentioning
confidence: 99%